2018
DOI: 10.1108/ijwbr-03-2017-0018
|View full text |Cite
|
Sign up to set email alerts
|

The winery experience from the perspective of Generation Z

Abstract: Considerations and Wine & Entertainment both perceived to be important but the winery's performance on the same was poor; Destination Attributes and Service Staff both perceived to be important with good performance; and Learning about Wine perceived unimportant with low performance. Originality/value-This is the first academic study focusing specifically on the winery experience from the perspective of Generation Z. As such it has provided new and useful insights for researchers and managers in the wine indus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 48 publications
(80 reference statements)
1
20
0
1
Order By: Relevance
“…Millennials were willing to pay more for wine with sustainability attributes than older generations and Baby Boomer were more interested in country appellation than younger generations. The first published wine research study on the Gen Z cohort was completed in Northern Greece (Stergiou et al , 2018) examining their desired wine tourism factors. Results showed that these young adults were most interested in wine tourism experiences that were cost-effective, provided good service and entertainment.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Millennials were willing to pay more for wine with sustainability attributes than older generations and Baby Boomer were more interested in country appellation than younger generations. The first published wine research study on the Gen Z cohort was completed in Northern Greece (Stergiou et al , 2018) examining their desired wine tourism factors. Results showed that these young adults were most interested in wine tourism experiences that were cost-effective, provided good service and entertainment.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Generational cohort theory (Wolf et al , 2018) has also been a useful concept when applied to the wine industry and analysis of wine consumer preferences and behaviors, though at times the concept is combined with other theories such as consumer lifecycle or life-stage theory (Fountain and Lamb, 2011; Johnson and Bruwer, 2003; Lockshin and Corsi, 2012; Wolf and Carpenter, 2005; Thach and Olsen, 2004; Olsen et al , 2007; Agnoli and Begalli, 2011; De Magistris et al , 2011; Charters et al , 2011; Mueller et al , 2011; Trait et al , 2019; Stergiou et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It appears that the application of importance-performance analysis in the context of wine tasting rooms has been limited. One notable exception is the study by Stergiou et al (2018). In their paper, the sample population consisted of 306 students who visited wineries in the Achacia region of the Peloponnese in Greece.…”
Section: Context Of Wine Tasting Roommentioning
confidence: 99%
“…The increasing significance and expansion of wine tourism has been followed by a substantial growth in related research. The cellar door remains a major focus of research, and many researchers have taken an experiential approach to wine tourism (Santos et al, 2019;Stergiou et al, 2018;Vo Thanh and Kirova, 2018).…”
Section: Introductionmentioning
confidence: 99%